Dyeability Improvement of Cotton Fabric by Electron Radiation Treatment - Davodiroknabadi, Abolfazl; Rashidi, Abosaeed; Mirjalili, Mohammad; Zohoori, Salar (Asian Journal of Chemistry, 2012)
Electron radiation is one of the finishing processes that can be used in dry environments and doesn't need any chemical materials and use for improving of textiles properties and synthetic polymers. Another important improvement of this finishing method is no need of water, less wastewater without any ecological problems. In this paper, the samples treated by 5, 10, 15, 20, 25, 30 and 35 KGy radiation intensities and they dyed with C.I. Direct Red 23. Also the physical properties of samples such as elongation, work of rupture and strength were investigated. The results show a significant improvement in dyeability of treated samples. Meanwhile, in this study the physical properties of samples investigated in order to find the best and ideal irradiation intensity.